Hmong Political Involvement in St. Paul, Minnesota and Fresno, California - Yang Lor (Hmong Studies Journal, 2009)
Over the past several years, Hmong in the United States have gained prominence for their increasing involvement in politics. Most of the attention has understandably focused on Fresno, California and St. Paul, Minnesota, home to the two largest Hmong populations in this country. While the Hmong communities in both cities are similar in size and have made significant political progress as evidenced by the election of Hmong candidates, the Hmong community in St. Paul has made greater inroads in the political realm. In addition to the elections of two Hmong candidates to the Minnesota State Legislature and two to the St. Paul School Board, the Hmong community in St. Paul has been able to engage local and state governments in Minnesota to address issues that affect the Hmong community. Through interviews, census data, and newspaper coverage of political campaigns, I show that Hmong in St. Paul have achieved greater representation in local and state governments and received greater support from government officials than Hmong in Fresno because Minnesota offers a social, economic, and political context that is favorable to fostering Hmong political involvement. Compared to Hmong in Fresno, Hmong in St. Paul have higher levels of socioeconomic resources and are more visible given their large size relative to other minority groups. They live in a region with consistently high levels of political participation and have political candidates who devote resources to mobilizing the Hmong community. Moreover, the Hmong vote has been critical to the success of Hmong candidates in St. Paul, an indication of the increasing political clout of the Hmong community there and a major reason why politicians in Minnesota are more willing to respond to issues that affect the Hmong community. Overall, this study highlights the importance of local and regional context in understanding the political incorporation of immigrants.